Burnout syndrome in athletes and their association with body image dissatisfaction at a private university - Baella-Vigil, G. V.; Hurtado-Bocanegra, M.; Marroquin-Quintana, J.; Rojas-Fernández, M. V.; Rosales-Medina, J. M.; Urbina-Rodriguez, J. C.; Tarabay-Barriga, A. P.; Carreazo, N. Y. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Burnout syndrome, from the sporting point of view, is the integration of both physical and emotional signs, caused by the high demands in competition. According to several studies, the prevalence of burnout syndrome is influenced by several factors that would lead to athlete`s body image dissatisfaction. METHODS: The study design is cross-sectional analysis. The study sample was 352 athletes selected from the Universidad Peruana de Ciencias Aplicadas (UPC). The main variables of this study are the burnout syndrome; which was measured by Athlete Burnout Questionnaire (ABQ) and body image dissatisfaction, through thirteen Scale drawings contour figure Gardner. To find the association between body image dissatisfaction and burnout syndrome Poisson regression was used. RESULTS: Athletes with burnout syndrome have 1.08 times more likely having body image dissatisfaction with a value P=0.011 (95% CI: 1.02-1.15). It was also found that a sport collectively practiced is a protective factor for Burnout Syndrome with P=0.015 (95% CI: 0.4-0.9). CONCLUSIONS: Relation between burnout syndrome and body image dissatisfaction in athletes was found. In addition, a relationship between practicing an individual sport and burnout syndrome was also found. More studies are necessary to confirm these relationships.